The Effect of Picture Media in Writing Descriptive Text Writing Skills In Grade 4 Students at SD Negeri 5 Bulungcangkring - Rohmawati , Mely; Adhelia Putri Febrianti; Salma Aulia Rahmadani; Dika Aida Husna; Nida’ Khusnun Nabila; Linda Dwi Cahyani; Silvia Devi Agustin; Denni Agung Santoso (Jurnal Disastri (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2024)
This study aims to explore the effect of picture media on students' descriptive text writing at SD Negeri 5 Bulungcangkring. The researcher looks more deeply at how the use of image media can affect the learning process of writing student descriptive texts. The method used in this research is quantitative with experimental research type. The research data was in the form of test questions. The population in this study were grade IV students of SDN 5 Bulungcangkring totaling 26 people, while the samples in this study were grade IV students with 14 male students and 12 female students. The data analysis technique used is the Independent-Sample t Test. The results of this study indicate that the use of image media in learning the skills of writing descriptive text essays provides varying results depending on the indicators measured. There are four indicators measured in this study. The following are the results, (1) Image Suitability, the statistical test results show that there is no significant difference between male and female students (Sig. = 0.630). The variance between the two groups was also homogeneous (Sig. = 0.683), (2) Spelling Accuracy, the results obtained showed a significant difference between male and female students (Sig. = 0.000). Male students tend to show a better level of spelling accuracy than female students. Although the variance was homogeneous (Sig. = 0.331), (3) Neatness, although the variance was not homogeneous (Sig. = 0.042), the t-test results showed that there was no significant difference between male and female students (Sig. = 0.107), and (4) Descriptive Ability, the statistical test results showed that there was no significant difference between male and female students (Sig. = 0.081). The variance between the two groups was also homogeneous (Sig. = 0.919).